A Study of Outcome-Based Educational Management in Community Schools of Kachin State, Northern Myanmar - Kote , Yar; Mangkang, Pojanee; Piboon, Suphak (Sripatum Review of Humanities and Social Sciences, 2026)
This study investigated the current status of Outcome-Based Educational Management (OBEM) and developed evidence-informed guidelines for its implementation in community schools in Kachin State, Northern Myanmar. Using an explanatory sequential mixed-methods design, data were collected from 112 educational stakeholders through a structured questionnaire, followed by focus group discussions with seven key informants. Quantitative data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analyses in SPSS, while qualitative data were analyzed thematically. The findings showed that overall OBEM implementation was perceived as high (M = 3.62, SD = 0.86). Among the three dimensions, Strategic Management (Process) received the highest rating (M = 3.80, SD = 0.86), followed by Readiness for OBE (Inputs) (M = 3.53, SD = 0.84) and Performance Results (Outcomes) (M = 3.52, SD = 0.88). Correlation analysis revealed significant positive relationships among Inputs, Processes, and Outcomes (p < .001). Regression analysis indicated that Processes significantly predicted perceived Outcomes (β = .928, p < .001), whereas Inputs did not make a significant unique contribution after controlling for Processes. Qualitative findings highlighted resource and infrastructure constraints, assessment literacy needs, and the importance of collaboration and capacity building. Based on the integrated findings, seven evidence-informed guidelines were proposed to support more context-sensitive OBEM implementation in resource-constrained and conflict-affected community schools.